2010
DOI: 10.1063/1.3479928
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of surface roughness in Ti/Al/Ni/Au Ohmic contact to AlGaN/GaN high electron mobility transistors

Abstract: High responsivity of amorphous indium gallium zinc oxide phototransistor with Ta2O5 gate dielectric Appl. Phys. Lett. 101, 261112 (2012) Two dimensional crystal tunneling devices for THz operation Appl. Phys. Lett. 101, 263112 (2012) Threshold gate voltage and subthreshold swing of the ultrathin silicon-on-insulator field effect transistor: Analytical model J. Appl. Phys. 112, 124517 (2012) Performance and stability of solution-based cadmium sulfide thin film transistors: Role of CdS cluster size and fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 13 publications
1
49
0
Order By: Relevance
“…At such high temperatures, the sheet resistance (R sh ) of the GaN based heterostructures can increase, 10,11 which may lead to higher on-state resistance (R on ) and limit the current delivery capability of transistors. 13,14 The rough surface may cause reproducibility and reliability issues, especially in highly scaled devices. 12 The high annealing temperature also causes the balling of molten Al due to its low melting point (660 C), which leads to a rough contact surface.…”
Section: Introductionmentioning
confidence: 99%
“…At such high temperatures, the sheet resistance (R sh ) of the GaN based heterostructures can increase, 10,11 which may lead to higher on-state resistance (R on ) and limit the current delivery capability of transistors. 13,14 The rough surface may cause reproducibility and reliability issues, especially in highly scaled devices. 12 The high annealing temperature also causes the balling of molten Al due to its low melting point (660 C), which leads to a rough contact surface.…”
Section: Introductionmentioning
confidence: 99%
“…The as-deposited (not annealed) sample showed a rectifying character. The van der Pauw Hall mobility measurement showed that the sheet density of carriers beneath the metal contacts remained on the same level of 9×10 12 cm…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a smooth surface morphology must be guaranteed because it closely related with an excellent ohmic contact. 30,31 Fig. 7 shows the typical AFM surface morphology images of 5 Â 5 lm 2 scan area for two structures, respectively.…”
Section: E Afm Characterizationmentioning
confidence: 99%